Unions, the High-Wage Doctrine, and Employment. - Gallaway, Lowell E. (CATO Journal)
Part of a special issue on whether unions are good for America. The writer examines the reasons for the creation of the present era of public protection of labor unions and its effect on the American economy. He traces the events surrounding the conception and popularity of the high-wage doctrine in the 1920s, just before the onset of the Great Depression. The writer discusses issues related to the subsequent New Deal, labor policy, and unemployment; the prevailing intellectual climate; the effects of World War II and its aftermath; and the disregard of evidence against the high-wage doctrine. He concludes that ongoing adherence to this incorrect doctrine is likely to have negative consequences for the U.S. economy, just as it did in the 1930s.